Assessment of genetic relatedness among Indian mustard (Brassica juncea) genotypes using morphological traits and DNA marker - Gupta, Ramwant; Chandrashekhar, U S; Yadav, J B; Chakrabarty, S K; Dadlani, M (The Indian Journal of Agricultural Sciences, 2012)
The genetic diversity and relatedness of 17 Indian mustard (Brassica juncea (L.) Czern & Coss) genotypes were assessed with morpho-physiological characteristics and 10 RAPD markers. Molecular parameters, viz. total number of bands, average polymorphic band, average per cent polymorphism, average polymorphic information content (PIC), average expected gene diversity (Hi), Jaccard’s similarity coefficient, principal coordinate analysis (PCA) and dendrogram generated using RAPD markers. Ten RAPD primers generated 62 loci with 50 polymorphic and 12 monomorphic showing 6.2 loci per primer. Primer OPB-01 showed maximum polymorphism (100 %) with maximum PIC (0.95) and Hi (0.33) value. Pusa Jaikisan and Kranti showed maximum similarity coefficient (0.81) while Varuna and Ogura were most distant (0.47), which was further confirmed by their morpho-physiological characteristics, viz. plant height, days to flowering (50%), days to maturity and 1000-seed weight. Seventeen Indian mustard genotypes were grouped into three major clusters I, II and III based on RAPD profiling. The cluster analysis was comparable up to some extent with Principal Coordinate Analysis (PCA) of two and three dimensional plots.